Digitalizacija javne uprave in Mestne občine Ljubljana - Cerar, Matej (Javna uprava, 2023)
Digitalisation has emerged as a principal subject of interest in both academic and business world. Yet the digital development of cities has received scant research attention, with only a fraction of all the research on digitalisation is directed towards public administration. The article begins by clarifying the distinction between digitalisation and digital transformation. It then outlines the European Union’s digital strategies and Slovenia’s national approaches, emphasizing goals related to digitalisation, transformation, and smart cities. Subsequently, the main aspects of the City of Ljubljana Digital Development Strategy for 2023–2027 are presented. Finally, the article provides insights into good e-governance and the role of modern technologies in it.
Keywords: digitalizacija; digitalne strategije; e-uprava; javna uprava; Mestna občina Ljubljana